The grid (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2020)
This paper aims to reflect about the syntactic experimentation in visual composition by arguing the role of the ‘grid’, the formal link created by the repetition and intersection of two or more series of parallel, perpendicular or generic straight lines on a surface. The grid is both a rule of syntactic construction and a visual figure expressed, especially in our modern age, in countless artistic works. The elements that make up a grid are a ‘reticle’, creating the ensemble of straight lines‒bands and their points of intersections, and the ‘mesh’, which is the ensemble of the surface units surrounded by the reticle. In the more common case of a binary grid, when the sequence of the rectilinear series has a continually equal rhythm in two directions, then the grid is modular; if the series are also orthogonal they produce a more common grid: the square grid. As indicated by Klee, a ‘grid’ can be created by dynamically crossing the most ‘primitive structural rhythms’: the rectilinear rhythm from top to bottom, and its homologous rhythm from left to right. Since they are the ‘sum of equal units’ repeated in two directions they produce rhythmic control of the plane through its measured occupancy. The structural features of the grid are being ‘multipliable’ and ‘divisible’ that permit increments or partial fragmentation without altering the rhythmic principle. The grid is, therefore, the figure of ‘possession’ of a flat surface by a system of straight lines. It can in fact unfold on the whole plane based on the endless underlying pattern of its coordinates, each time choosing which traces to use to become visible. Through the reticle, the logical‒formal procedure of repetition, possessed by the grid like a genetic attribute, becomes the syntactic‒compositional rule metaphorizing the plane tout court with a radical figurative elementarism.
Keywords: figurative syntax; reticle; square mesh; visual composition